Fundamentals of structural integrity : damage tolerant design and nondestructive evaluation - Grandt, A. F. (Alten F.), 1945- (New Delhi : Wiley, 2004)
Discusses applications of failures and evaluation techniques to a variety of industries. * Presents a unified approach using two key elements of structural design.
PART I. INTRODUCTION. -- Chapter 1. Introduction. -- Chapter 2. Review of Preliminary Concepts. -- Chapter 3. Introduction to Linear Elastic Fracture Mechanics. -- Chapter 4. Nondestructive Evaluation. -- PART II. DAMAGE TOLERANCE ANALYSIS. -- Chapter 5. Crack Tip Plasticity. -- Chapter 6. Fracture and Residual Strength. -- Chapter 7. Fatigue Crack Growth. -- Chapter 8. Stress Intensity Factor Analysis. -- Chapter 9. Service Induced Damage. -- PART III. NONDESTRUCTIVE EVALUATION. -- Chapter 10. Visual and Penetrant Inspection. -- Chapter 11. Radiography. -- Chapter 12. Ultrasonic Inspection. -- Chapter 13. Eddy Current.-- Chapter 14. Magnetic Particle Inspection. -- Chapter 15. Other Inspection Methods. -- PART IV. APPLICATIONS. -- Chapter 16. Design Considerations. -- Chapter 17. Structural Integrity of Aging Systems. -- Chapter 18. Concluding Remarks. -- Appendix. AFGROW Users' Guide.
Includes bibliographical references and index.
Keywords: Airplanes -- Materials -- Testing; Airframes -- Design and construction; Nondestructive testing; Fault tolerance (Engineering); Structural analysis (Engineering)